The Effect of Perineal Massage on Perineal Status and Duration of Labor - Haryanti, Priyani (Jurusan Keperawatan FIKES UNSOED, 2019)
Perineal rupture in postpartum mothers causes bleeding, pain, and high dependency on others after the birth. The preliminary study results showed that 68.81% of postpartum mothers experienced perineal rupture. The aim of this study was to determine the effect of perineal massage on perineal status and length of labor. It was quasi-experimental research with control group post-test only design. The population were all expectant mothers in the Yogyakarta Community Health Center. A sample of 60 respondents were divided into control and intervention groups using a random sampling method. The inclusion criteria were 20-35 years old, singleton pregnancy, spontaneous labor, and gestational age of 34-36 weeks. The study instrument used was an observation sheet. Data were analyzed using descriptive, t-test independent, Mann-Whitneyâ€™s, and linear regression test. Results. The results showed that perineal massage affects perineal status (p < 0.001) and the duration of stage I andÂ stage II of labor (p < 0.001). Perineal massage affects perineal status and the duration of labor in the Yogyakarta City Community Health Center.